PAI Teacher’s Readiness In Implementing The Independent Curriculum Learning At SMP Negeri 2 Bulu - Ilma Salzalin Husna; Nurul Latifatul Inayati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
In 2019, the Republic of Indonesia's Ministry of Education and Culture made a point of highlighting new educational initiatives, one of which was the Free Learning Curriculum. During the Covid 19 epidemic, the Free Learning Curriculum seeks to revive education. The interview approach is the one applied in this study. In order to understand more about the PAI Teachers' readiness to execute the autonomous learning curriculum, interviews were conducted. According to the findings of this study's research, grade 7 PAI teachers were given the autonomous learning curriculum's introduction stage whereas grades 8 and 9 PAI instructors were not yet ready to accept it.